The relationship between learning and thinking styles and the performance achievement in 110m hurdles running among second-stage students at the College of Physical Education – University of Koya - كريم, فرهاد أبراهيم (Sulaimani Journal for Humanities, 2025)
This study aimed to identify the patterns of learning and thinking in the research sample. Secondly، for recognition of the level of achievement of second-stage students of School of physical education/ Koya University in (110m) hurdles. Lastly، to identify the correlation between the learning patterns and thinking with the achievement of the research sample in (110m) hurdles. The researcher used the descriptive approach for its suitability and the nature of the research. The sample of the research were (24) students (2nd stage) at School of Physical Education/ Koya University. And to identify the strength and direction of the correlation between the learning patterns, thinking and achievement of (110 m) hurdles of the members of the research sample, In order to achieve the objectives of the study and to test its hypothesis of the study of correlational relations, and by analyzing the results and discussing the results performing the Pearson correlation coefficient, a significant relationship was found between the learning patterns and thinking with the students' achievement in 110 m hurdles. Several conclusions were reached: 1- The number of students using the right pattern (10) students, while the number of students using the left-pattern users (14) students. 2- None of the students were using the integrated pattern of the research sample. 3- A positive relationship was found between learning pattern and thinking with the achievement of 110m hurdles in the research sample. In light of the conclusions, the researcher recommended the following: - The need for the lecturer or the instructor to inform the students to help students for using the right and left hemisphere as consistently as possible. - Familiarity of lectures with learning patterns and prevailing thinking which is possessed in students. - The attention of workers who work in the education and training field to prevailing thinking patterns because of its importance in achieving better results as well as its role in keeping pace with contemporary scientific development. - Conducting similar studies in which sports activities and games other than those used in the current research (such as throwing and jumping) as well as the collective games. - The need for studies on older samples to include all university students.
Keywords: learning patterns and thinking; achievement; 110m hurdles